2021
DOI: 10.46244/geej.v8i1.1240
|View full text |Cite
|
Sign up to set email alerts
|

Changing Belief of Pre-Service English Teachers During Teaching Practicum

Abstract: This study investigated the changing belief of pre-service English teachers during they did teaching practicum. It was one of subjects in teacher education programs. Belief of pre-service English teachers played significant role as it could influence their classroom practices and teaching outcomes. The methodology of research used in this study was qualitative case study. It involved twenty pre-service English teachers from English Department. They were put in twelve schools which located in four towns in Bant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Thus, the change in belief for the better could help teachers adjust appropriate education policies to improve the quality of English teacher education, especially in the Chinese context. Similar research was conducted in the Indonesian setting; Heryatun and Damanik (2018) discovered that prior learning experiences significantly contributed to pre-service teacher beliefs following the completion of the teaching practicum in the Indonesian setting. Their results indicated that teaching practice has the most significant influence on pre-service teachers’ beliefs.…”
Section: Literature Reviewmentioning
confidence: 68%
“…Thus, the change in belief for the better could help teachers adjust appropriate education policies to improve the quality of English teacher education, especially in the Chinese context. Similar research was conducted in the Indonesian setting; Heryatun and Damanik (2018) discovered that prior learning experiences significantly contributed to pre-service teacher beliefs following the completion of the teaching practicum in the Indonesian setting. Their results indicated that teaching practice has the most significant influence on pre-service teachers’ beliefs.…”
Section: Literature Reviewmentioning
confidence: 68%